ACOUSTO-OPTICS : Acousto-optic modulators based on a KYW crystal. (28th July 2017) - Mazur, M M; Mazur, L I; Pozhar, V E; Shorin, V N; Konstantinov, Yu P
Abstract: Two types of acousto-optic modulators based on new acousto-optic crystals KY(WO4 )2 are developed and experimentally investigated. Their characteristics are compared with those of existing acousto-optic quartz modulators. It is shown that the new modulators provide an almost 10-fold efficiency gain, which eliminates the need for water cooling of such devices.